KEPUASAN PENGGUNA DITINJAU DARI KREDIBILITAS STAF LAYANAN DI PERPUSTAKAAN DAN PUSAT INFORMASI ILMIAH FAKULTAS EKONOMI UNPAD - Rachmawati, Tine Silvana; Rodiah, Saleha; Kartika H, Ainun (Edulib, 2017)
Abstract. The purpose of study was to determine user satisfaction toward credibility of staff library service at Library and Scientific Information Center at Economics and Business Faculty, University of Padjadjaran (FEB UNPAD). The research of library staff's credibility based on perceptions and expectations (minimum and maximum expectations). There are three components to measure in this study:(1)Trustworthiness, (2) Expertise, and (3) Fascination. The population in this study is determined based on the number of users who come to the P2I2 of FEB UNPAD. Sampling technique that used in this study is Purposive Sampling with 99 people as sample. Data was collected by questionnaire, conduct observation, and literature study. The results showed that overall users are coming to the P2I2 of FEB UNPAD were satisfied with the services. This user satisfaction based on the gap (gap) between the perceptions and expectations of service users indicates that the P2I2 of FEB UNPAD has good credibility and is in " zone of tolerance ", in other words the services provided by library's staff at Faculty of Economics and Business, Padjadjaran University, has meet the user's expectations.